Book Review Sadaf Ahmad. Pakistani Women: Multiple Locations and Competing Narratives.: Oxford University Press, Karachi, 2010. pp x + 316 Illust. Notes. Gloss. Bibliog. Index. ISBN 978-0-19-5477054 - Zubair, Shirin (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
No abstract